An Analytical Study of the Status of Scientific Evidence in Understanding the Qur'an - Rubeena Shaheen; Hafiz Jamshed Akhtar (jihat-ul-islam, 2022)
This is the last revelation of the Qur'an revealed on the Prophet Muhammad (PBUH). The revelation which was started by prophesying to Adam. The Torah, the Psalms, the Gospels and the Quran are more prominent in the holy books of heavenly religions. With the development of world-class sciences and the emergence of new scientific facts, many of the statements made by the earlier modern books have been rejected by scientific evidence. There has also been a clash between sciences and religions. After the sixteenth century, science has gradually adopted its importance. And the church has not been the place that Christianity has been in its previous peak. What is important in this regard ís that the Qur'anic revelation is not relevant to science despite its importance, rather the Qur'an focuses on research and scientific evidence is helpful in understanding the Qur'an. However, some Muslim scholars have confusion with scientific evidence in the Quran. From the article below, the views of the legalists and the unbelievers are explained in detail so that the scholars and the public can be guided in adopting this modern style of Quran understanding.